Frequency and characteristics of hematologic and non-hematologic Bortezomib-related toxicity (Hematology Meeting Reports, 2009)
ortezomib (Velcade®) is the first of a new class of drugs known as proteasome-inhibitors. Its efficacy has been established in phase II trials SUMMIT and CREST and phase III trial APEX has demonstrated the superiority of Bortezomib (Velcade®) over high-dose dexamethasone in relapsed/refractory multiple myeloma (MM) patients. Although generally well tolerated, several side-effects are correlated to the administration of Bortezomib (Velcade®).